Benefits of rice technologies introduced by the Department of Agriculture on Rice Farming in selected barangays in Guimbal, Iloilo - Mamades, Teodora G. (2003)
The study was conducted to determine primarily the effects/benefits of the Department of Agriculture (DA) introduced rice technologies over the lives of the farmers in terms of their total production and increase in income per cropping in selected barangays in Guimbal, Iloilo. The data were gathered through personal interviews with 59 farmer respondents using the prepared questionnaire, which was translated into a local dialect to ensure clear understanding of the respondents. The result of the study revealed that all of the respondents have been engaged in rice farming as their main sources of income. Of the total respondnets, aside from rice farming, two have been engaged in corn and vegetable farming, two respondents are engaged in business, one is a utility worker and two are drivers. With the exsting rice technologies or farm practices by the farmers, 100% signified of their awreness of the DA introduced rice technologies. They further confirmed that these are adaptable in the study sites. This DA introduced rice technologies include utilization of fertilizer, High Yielding Variety (HYV) of rice as well as employing the weeding practices. On the fertilizer utilization and weeding practices employed by the farmers, the results revealed that the combined organic and inorganic fertilizer as well as the hand weeding or spraying of herbicides greatlt help in the increase of production. With the adoption of these technologies, regardless of the cropping pattern and cropping season the farmers emphasized its contribution in the increase of income. However, 80% say that high costs, limited supply and untimely delivery of production inputs particularly HYV seeds affect the planting schedule, which thereby affecting the volume of production. Further study shall be conducted on this regard, to include new technologies for improving farm productivity and profitability of the farmers. Despite some issues raised by the farmer respondents 100% claimed that in the absence of the DA introduced technologies, their production would not be improved. According to them, adoption of the DA introduced rice technologies helped boost their production thereby increasing their income.
Research Paper (Mgt 299 - Research Methods in Management). --[Iloilo City] : UPV-CM, July 2003.